Pengaruh Akuntabilitas, Transparansi, dan Kepemimpinan terhadap Efektivitas Pengelolaan Dana Desa di Kabupaten Dharmasraya - Sari, Putri Maya; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2025)
This research is motivated by the rampant corruption cases lately in Dharmasraya district. The purpose of this study is to determine the effect of accountability, transparency and leadership on the effectiveness of village fund management. The type of research conducted is quantitative research. This study uses primary data in the form of distributing questionnaires to Village Heads, Village Secretaries, Village Treasurers, Welfare Section Heads, Government Section Heads, Service Section Heads, Planning Section Heads, and Village Assistants. The sample in this study was obtained by distributing 201 questionnaires and 197 questionnaires were processed. The data analysis method used is multiple linear regression analysis with the help of IBM SPSS software. The results of this study indicate that accountability, transparency, and leadership have an effect on the effectiveness of village fund management.